THE ROLE OF ADVANCED INTERNATIONAL EXPERIENCE IN IMPROVING PROSECUTORIAL VERIFICATIONS OVER THE IMPLEMENTATION OF LAWS - Djumayev Shokhjakhon Begimqul ugli (The Conference Hub, 2025)
This article discusses prosecutorial verifications of the execution of laws, their specific aspects and the classification of forms of prosecutorial supervision over the execution of laws. Some official statistical data on the conducted prosecutorial investigations are presented. A scientific discussion was held with the opinions of a number of legal scholars, and the author’s personal scientific and theoretical position on their views was presented. The best practices of a number of foreign countries, including Kazakhstan, Turkmenistan, Belarus, the USA, Great Britain, France, Singapore, Malaysia, were comparatively and legally analyzed with our national legislation, and proposals were put forward.
Keywords: prosecutor’s verifications over the execution of law, prosecutorial supervision, prosecutorial supervision over the execution of laws, monitoring, deadlines for conducting verifications, information-analytical activity.